Pilot Plant Pressure Oxidation of Refractory Gold-Silver Concentrate from Eldorado Gold Corporation’s Certej Project in Romania - T. Chan; M. Collins; J. Dennett; J. Stiksma; J. Ji; R. Kalanchey; R. Berezowsky (Canadian Institute of Mining, Metallurgy and Petroleum, 2014)
A pilot plant campaign has been conducted by Sherritt Technologies in support of Eldorado Gold Corporation’s evaluation of pressure oxidation technology for the treatment of refractory gold concentrates from the Certej deposit in Romania. Four separate concentrates, containing 3.5 to 5.4 g/t Au, 13.0 to 14.5% S2- and 12.0 to 32.5 g/t Ag, were tested in the eight-day campaign. The major gold-bearing mineral was pyrite. Preliminary batch tests indicated that gold extraction from the oxidized concentrates in subsequent cyanide leaching was adversely affected by the presence of organic carbon in the pressure oxidation feed when chloride in solution was at an elevated level. As such, the process conditions that were tested during the pilot plant operation were selected to either counteract the negative impact of the organic carbon, or to deactivate it during pressure oxidation. Both process routes proved feasible, yielding gold extraction of 95 to 98% in cyanide leaching of the oxidized concentrates. Silver extraction was typically in the range of 80 to 90%, provided that the oxidized concentrates were also processed in a lime boil step prior to cyanide leaching.